1993
DOI: 10.1002/pro.5560020810
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the structure of human basic fibroblast growth factor at 1.6 Å resolution and analysis of presumed heparin binding sites by selenate substitution

Abstract: The three‐dimensional structure of human basic fibroblast growth factor has been refined to a crystallographic residual of 16.1% at 1.6 Å resolution. The structure has a Kunitz‐type fold and is composed of 12 antiparallel β‐strands, 6 of which form a β‐barrel. One bound sulfate ion has been identified in the model, hydrogen bonded to the side chains of Asn 27, Arg 120, and Lys 125. The side chain of Arg 120 has two conformations, both of which permit hydrogen bonds to the sulfate. This sulfate binding site has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 62 publications
3
64
0
4
Order By: Relevance
“…Peptide mapping studies (Baird et al, 1988) have shown that a peptide related to residues 106 -115 of bFGF can inhibit the binding of 125 I-bFGF to its receptor. Subsequently, the threedimensional structure determination of bFGF (Zhang et al, 1991;Eriksson et al, 1993) suggested that these residues form an antiparallel ␤-turn on the surface of the molecule. To identify residues on bFGF for the receptor binding, the crystal structure is first subjected to molecular dynamics treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peptide mapping studies (Baird et al, 1988) have shown that a peptide related to residues 106 -115 of bFGF can inhibit the binding of 125 I-bFGF to its receptor. Subsequently, the threedimensional structure determination of bFGF (Zhang et al, 1991;Eriksson et al, 1993) suggested that these residues form an antiparallel ␤-turn on the surface of the molecule. To identify residues on bFGF for the receptor binding, the crystal structure is first subjected to molecular dynamics treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Alignment of amino acid sequences in aFGF and bFGF reveals that the residues comprising the heparin binding site 2Ј on bFGF correspond to Gln-63, Asp-68, Leu-72, and Gln-77 on aFGF, none of which are either basic or conserved residues (Eriksson et al, 1993). This argues against the possibility that these particular residues on aFGF interact with trisaccharide or heparin and likewise makes it difficult to reconcile the Ornitz model with the induction of FGF receptor dimerization by aFGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consensus histograms used in the test cases were generated from the atomic coordinates of ®broblast growth factor (4fgf; Eriksson et al, 1993) after removing the overall temperature factor from the electron-density map. Since 2D histograms are resolution dependent, several ideal histograms were generated for a range of resolutions from 4.0 to 1.5 A Ê using the method described by Goldstein & Zhang (1998).…”
Section: The 2d Histogram-matching Proceduresmentioning
confidence: 99%
“…HS-related GAG are known to interact with a wide range of growth factors and immunomodulatory cytokines, including the chemokines [10], IL-1, IL-2, IL-3, IL-6 [11], tumour necrosis factor (TNF) [12] and IFN-g [13]. The nature of this interaction is best understood for the basic fibroblast growth factor (bFGF) family [14], whose heparin-binding domain has been characterized [15]. In common with other heparin-binding proteins, bFGF binds to the GAG by electrostatic bonding to characteristic short clusters of basic amino acids [16].…”
Section: Introductionmentioning
confidence: 99%